Hyperbaric Oxygen Therapy Influence on Irradiated Bone Repair and Collagen Orientation (Research, Society and Development, 2020)
The present study aimed to evaluate the effects of HBO on bone repair after ionizing radiation, by using histomorphometry, computed tomography and polarization microscopy. Twenty male Wistar rats were used. One radiation dose (30 Gy) was administered on the left leg in all animals, and after 30 days, bone defects were created in both femurs. Then, 10 animals received daily HBO sessions (2.5 ATA for 90 minutes), and all animals were euthanized 5 or 7 days after surgery. The femurs were separated into 4 groups (n=5) for each euthanasia time interval: Control (Right femur: Non-irradiated and Non-HBO), RXT (Left femur: Irradiated and Non-HBO), HBO (Right femur: Non-irradiated with HBO), RXT+HBO (Left femur: Irradiated with HBO). The bone cortical and defects were evaluated. Data were analyzed using the Kolmogorov-Smirnov tests, unpaired t-test, and ANOVA with Bonferroni correction. Higher HU values and new bone formation were observed in Control and HBO groups, with improved repair. Group HBO showed predominant Yellow/Orange/Red birefringence of collagen in the defect area. HBO improved bone repair in physiological conditions, with increased blood vessels and bone formation. However, it was not efficient in improving repair and collagen orientation in bone after high doses of ionizing radiation.